The "Redlands Gang" (1944)
Members of the "Redlands Gang" were sent to Marine Officer Candidate School in New River, North Carolina, after their Cal Poly naval training. This photo appeared in the October 1944 issue of the Mustang Newsletter. The brainchild of Public Relations Director Robert E. Kennedy, the publication kept Cal Poly alums in touch during the war.